2021
DOI: 10.5946/ce.2020.065
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Fine Needle Aspiration Using a 22-G Needle for Hepatic Lesions: Single-Center Experience

Abstract: Background/Aims Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) has been accepted as a reliable tool in diagnosing and staging intra-abdominal tumors. In this study, we aimed to investigate the performance of EUS-FNA in the evaluation of liver masses and its impact on patient management and procedure-related complications retrospectively. Methods Data of patients who underwent EUS-FNA biopsies due to liver masses between November 2017 and July 2018 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In contrast, a prospective study reported the diagnostic accuracy of EUS-FNA in hepatic masses to be between 82% and 100% and the sensitivity, specificity, NPV, and PPV to be 94%, 100%, 78%, and 100%, respectively [ 13 ]. Additionally, EUS-FNA can produce specimens at the most comparable to the specimens obtained in percutaneous liver biopsy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a prospective study reported the diagnostic accuracy of EUS-FNA in hepatic masses to be between 82% and 100% and the sensitivity, specificity, NPV, and PPV to be 94%, 100%, 78%, and 100%, respectively [ 13 ]. Additionally, EUS-FNA can produce specimens at the most comparable to the specimens obtained in percutaneous liver biopsy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a prospective study reported the diagnostic accuracy of EUS-FNA in hepatic masses to be between 82% and 100% and the sensitivity, specificity, NPV, and PPV to be 94%, 100%, 78%, and 100%, respectively [ 13 ]. Additionally, EUS-FNA can produce specimens at the most comparable to the specimens obtained in percutaneous liver biopsy [ 13 ]. One study that directly compared percutaneous liver biopsy (60 patients) and EUS-FNA (30 patients) revealed that EUS-FNA has equivalent feasibility of histological diagnosis (percutaneous liver biopsy = 100% and EUS-FNA = 93%, p =0.841).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgastric and transduodenal approaches are used to visualize the left and right liver lobe, respectfully, bearing in mind that the right posterior segments are inaccessible for examination using this method [105]. The value of EUS in detecting and providing tissue diagnosis for liver lesions, most prominently metastases of solid tumors, as well as primary hepatic malignancies, has been shown in multiple studies [4] (Table 3) [106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. A recent review by Sbeit et al [122] reports the diagnostic yield of EUS-guided biopsy of focal liver lesions ranging from 89.7-100%, confirming the superiority of EUS sampling.…”
Section: Eus Fna/fnbmentioning
confidence: 99%
“…In this issue of Clinical Endoscopy, a study by Akay et al [ 5 ] evaluated the diagnostic capability of a single EUS-FNA puncture using a 22-gauge needle for focal liver lesions, which included 25 patients with liver lesions and a technical success rate of 88% (22/25). Of the 22 patients with successful EUS-FNA, the aspirate sufficiency and biopsy sufficiency rates were 94% (21/22) and 86% (19/22), respectively, even with a single pass of FNA.…”
mentioning
confidence: 99%